Australian climate concern and the 'attitude–behaviour gap'. Issue 4 (20th March 2016) - Higham, James; Reis, Arianne; Cohen, Scott A.
Abstract : Anthropogenic climate change poses considerable challenges to all societies and economies. One significant contributor to human-induced climate change is tourism transportation, particularly aviation. This paper addresses the relationship between climate change concerns, the energy-intensive nature of tourist consumption, and unrestrained tourist air travel behaviour in the context of Australia. Following Barr et al. [(2010). "A holiday is a holiday": Practicing sustainability, home and away. Journal of Transport Geography, 18 (3), 474–481], it seeks to understand public climate concern within the context of routine everyday ('home') lives and occasional tourist ('away') decision-making, with a specific focus on air travel. It draws upon 20 in-depth semi-structured interviews conducted in Australia between March and June 2011. The findings highlight the contradictory nature of environmental concerns and consumption decisions in everyday and tourist contexts. This is evident in widespread domestic consumer practices that are motivated, all or in large part, by climate concerns, set against almost complete disregard and neglect of responsibility to modify existing air travel practices. Our results highlight the magnitude of the challenge involved in shifting deeply entrenched air travel behaviours despite the growing urgency of radical emission reductions. It also highlights the need to consider consumer responses to climate change not in isolation, but in relation to industry drivers and strong government policy interventions.